High and Low Taxa Specificity of Rhizosphere Bacteria Communities of Mangrove (Rhizophora mucronata) from Kuala Langsa and Telaga Tujuh Island, East Aceh - Maysaroh, Siti; Samira Ismet, Meutia; Andini, Rita; Anggraini, Nurlita; Subhan, Beginer (Faculty of Fisheries and Marine Universitas Airlangga, 2024)
Highlight Research Bacteria from mangrove sediment have been identified, and environmental parameters have been analyzed. The relationship between rhizosphere bacteria and the environment has been analyzed. The distribution and abundance of rhizosphere bacteria differ between Kuala Langsa and Telaga Tujuh. The diversity and abundance of rhizosphere bacteria are not influenced by environmental parameters. Abstract The focus of this study on understanding the structure and dynamics of rhizosphere bacteria in mangrove ecosystems is driven by the increasing acknowledgment of the crucial roles these microorganisms play in ecosystem functioning. Rhizophora mucronata, a key mangrove species, is known for its ecological significance. Investigating the bacteria associated with its rhizosphere offers valuable information about the symbiotic relationships between mangrove vegetation and microbial communities. Bacteria are vital for decomposition and nutrient availability in mangroves. This research examines sediment from rehabilitated and natural areas to understand how human and natural factors shape bacterial communities.The DNA sequence was analyzed using Next-Generation Sequencing (NGS), which targeted the 16S bacterial region in the V3-V4 rDNA. Additionally, environmental factors such as nitrate, phosphate, and sulfur content were also analyzed. Kruskal-Wallis and T-test statistical analyses were used to examine the abundance of bacteria and environmental parameters between study sites.There are differences in the types of bacteria found in Kuala Langsa and Telaga Tujuh. Approximately 7% of the rhizosphere bacterial groups were exclusively detected in Telaga Tujuh, such as Fusobacteriia (Class). Additionally, the abundance of bacteria at both locations differs significantly (p < 0.05), as determined by Kruskal-Wallis. The results of the t-test indicate that the observed environmental parameters do not differ significantly from each other. The environmental parameters studied did not significantly impact the types or abundance of detected rhizosphere bacteria.